PENGENDALIAN GERAK MOBILE ROBOT BERBASIS BCI (BRAIN COMPUTER INTERFACE) - Adbizar Asmon Rizal; Sastra Kusuma Wijaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Has long been known that neurons in the human brain produces electrical waves that can be measured, these waves obtained by the Emotiv EPOC + to get a signal Electroencephalography (EEG) of 14 pieces of electrodes distributed along the human scalp. Brain Computer Interface (BCI) is a system that allows the control hardware using human brain signals using Electroencephalography (EEG). Brain Computer Interface can be used to control a variety of microcontroller-based devices such as mobile robot control, a robot arm, and wheelchairs to help disabled people. In this study, we developed a system that allows humans to control the direction of motion of the mobile robot wave Electroencephalography (EEG). The system consists of an Emotiv EPOC + Neuroheadset, computers, and mobile robots. Cognitive Suite provided by Emotiv is responsible for generating the necessary control measures to make the mobile robot to perform three different orders: move forward, turn right, and turn left. The experimental results show that the mobile robot can be controlled in real-time based on physiological changes the subject. Keywords: Brain Computer Interface, Emotiv EPOC+, Mobile Robot, Microcontroller.